PEMBERDAYAAN SDM DALAM PENGARUSUTAMAAN GENDER - Mardiana Mardiana; Tuti Khairani; Seno Andri (JIANA ( Jurnal Ilmu Administrasi Negara ), 2017)
Empowerment of Human Resources in Gender Mainstreaming. This study aims to analyze the implementation of immunization and factors affecting the empowerment of human resources in gender mainstreaming in the Office of Women’s Empowerment and Child Protection. The research informants were Head of Department, Head of Division and Head of Women Empowerment. Data collection techniques in this study using questionnaires, interviews, and observations. Data analysis in this research using interactive model analysis include data reduction phase, data presentation and data verification to draw conclusion. The results show that all activities planned in the Strategic Plan of the Office of Women’s Empowerment and Child Protection are mostly implemented. In addition, some women empowerment programs have been successfully implemented, just not succeeded in realizing gender equality. While the inhibiting factor of the implementation of human resource empowerment program in mainstreaming gender is the minimum budget allocated.